2006
DOI: 10.1007/s00702-006-0604-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation during mental rotation in school children and adults

Abstract: Summary Mental rotation is a complex cognitive skill depending on the manipulation of mental representations. We aimed to investigate the maturing neuronal network for mental rotation by measuring brain activation in 20 children and 20 adults using functional magnetic resonance imaging. Our results indicate that brain activation patterns are very similar between children and adults. However, adults exhibit stronger activation in the left intraparietal sulcus compared to children. This finding suggests a shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 64 publications
2
38
0
2
Order By: Relevance
“…The group of healthy comparison participants also showed significant deactivations in the angular gyrus, as well as in the precuneus, posterior cingulate, and temporal regions. These findings are in line with the previous studies (Jimenez et al, 2010;Kucian et al, 2007). Although the relative deactivations seen in the NTR group were more limited than those observed in controls, the general pattern resembled more the pattern observed in healthy controls than the TR-C group did (Figure 1 and Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…The group of healthy comparison participants also showed significant deactivations in the angular gyrus, as well as in the precuneus, posterior cingulate, and temporal regions. These findings are in line with the previous studies (Jimenez et al, 2010;Kucian et al, 2007). Although the relative deactivations seen in the NTR group were more limited than those observed in controls, the general pattern resembled more the pattern observed in healthy controls than the TR-C group did (Figure 1 and Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have compared the brain networks involved in mental transformations in adults and children (Funk et al 2005;Kucian et al 2007) but to our knowledge, none have made a comparison between young adults and elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies tested children's performance on various 2-D stimuli using animal drawings or other familiar objects, alphanumeric stimuli, or abstract characters, and showed that various 2-D stimuli differ in their difficulty level. Performances for familiar 2-D stimuli (e.g., animal drawings or alphanumeric stimuli) were found to elicit higher accuracy scores and shorter response time as opposed to abstract characters [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%